Campaign Management System with Big Data Analytics in Marketing Products through Digital Channel - Nurninawati, Euis; Soedaryono, Chaidir Kurnia Thoullah; Hamzah, Muzaffar (PT. Riset Press International, 2023)
Data is the new gold in the industrial revolution era 4.0, with the development of internet-based technology, big data, blockchain etc. a lot of data is created from this process, as well as in the banking world a lot of data is created from transactions made by customers and demographic data created when customers opening banking products, this can help companies understand client desires in meeting their financial needs, big data is the right tool for processing large data within companies and can help companies make decisions, one of the company's obstacles is in marketing their products to customers during the Covid 19 pandemic, the disconnection of interaction with customers directly affected company sales, especially banking, the infrequency of customers coming to branches resulted in difficulties for marketing companies and explaining products to sell to customers. With a campaign management system that can transmit to customers via digital channels such as WhatsApp, email and SMS and supported by big data technology, it will help companies sell products without having to interact directly, this can increase company profits and can help customers in their financial needs.